S31 Prognostic value of interferon gamma release assays and tuberculin skin test in predicting the development of active tuberculosis: the uk predict tb cohort study. (15th November 2017) - Abubakar, I; Drobniewski, F; Southern, J; Sitch, AJ; Jackson, C; Lipman, M; Deeks, JJ; Griffiths, C; Bothamley, G; Lynn, W; Burgess, H; Mann, B; et al.
Abstract : Background: Tackling tuberculosis (TB) requires testing and treatment of high-risk groups for latent tuberculosis infection. We estimated the predictive values of the tuberculin skin test (TST) and interferon gamma release assays (IGRAs) for development of active TB in migrants and contacts of active TB patients in the UK. Methods: Participants were prospectively recruited in clinics and the community and followed for a median of 2.9 years. We administered IGRAs (Quantiferon Gold In-Tube [QFT-GIT] and T-SPOT. TB ) and TST (with 3 thresholds: 5 mm (TST 5 ), 10 mm (TST 10 ) and TST 15 (5 mm in BCG-naïve, 15 mm in vaccinated). Potential incident TB cases were identified by telephone interview and national TB databases and confirmed by medical note review. Results: Ninety-seven (1.0%) of 9610 participants developed active TB (77 of 6386 who had Results for T-SPOT. TB, QFT-GIT and TST). All tests had very low incidence in test negatives (1.2–1.6 per 1000 per year). Incidence rates in test positives were highest for TSpot. TB (13.2 95% CI: (9.9–17.4)), TST 15 (11.1 (8.3, 14.6)) and QFT.GIT (10.1 (7.4, 13.4)); positive test Results for these tests were significantly more predictive of progression than TST 10 and TST 5, TSpot. TB was also higher than QFT.GIT. TST 5 predicted more at high risk (55%) than TST 10 (45%), TSpot. TB (33%), TST 15 (38%) and QFT.GIT (31%). Conclusions: IGRA-based or TST 15 strategies are most suited for population screening in low-risk populations. Although TST 5 and TST 10 detect more TB cases this is at the cost of more individuals being classified at high risk with lower positive predictive values.